Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/cbdv.202000839
|View full text |Cite
|
Sign up to set email alerts
|

New Pyrano‐4H‐benzo[g]chromene‐5,10‐diones with Antiparasitic and Antioxidant Activities

Abstract: New pyranonaphthoquinone derivatives were synthesized and investigated for their activity against Trypanosoma brucei, Leishmania major, and Toxoplasma gondii parasites. The pentafluorophenyl derivative was efficacious against T. brucei with single digit micromolar EC 50 values and against T. gondii with even submicromolar values. The 3-chloro-4,5-dimethoxyphenyl derivative showed an activity against amastigotes of Leishmania major parasites comparable to that of amphotericin B. In addition, antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Animal model studies and molecular analyses of human tumors have indicated that many of these regulators are altered in cancer, particularly, CDK4, CDK6 and CDK2 and their substrates, which control progression through the G1/S phases of cell-cycle division. A literature survey confirmed that CKD2 is a valid target for 4 H -pyran derivatives ( Figure 2 ) with anticancer activities [ 33 , 34 , 35 , 36 , 37 ]. Therefore, to investigate whether or not the cellular mechanism by which the most active cytotoxic derivatives 4d and 4k suppressed the proliferation of HCT-116 cells is related to the inhibition of CDK2, the induced-fit docking approach in the ATP active site of the enzyme using the Glide program of Schrodinger-Maestro 11.2 was employed prior to the in vitro inhibitory kinase assays.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Animal model studies and molecular analyses of human tumors have indicated that many of these regulators are altered in cancer, particularly, CDK4, CDK6 and CDK2 and their substrates, which control progression through the G1/S phases of cell-cycle division. A literature survey confirmed that CKD2 is a valid target for 4 H -pyran derivatives ( Figure 2 ) with anticancer activities [ 33 , 34 , 35 , 36 , 37 ]. Therefore, to investigate whether or not the cellular mechanism by which the most active cytotoxic derivatives 4d and 4k suppressed the proliferation of HCT-116 cells is related to the inhibition of CDK2, the induced-fit docking approach in the ATP active site of the enzyme using the Glide program of Schrodinger-Maestro 11.2 was employed prior to the in vitro inhibitory kinase assays.…”
Section: Resultsmentioning
confidence: 97%
“… Examples of pyran-containing compounds with antibacterial [ 33 ], antioxidant [ 34 ] and anticancer activities via inhibition of CDK2 [ 35 , 36 , 37 ]. …”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lawsone has been used to prepare naphtho[2,3-b]furan-4,9-dione derivatives via transition metal-free tandem formal [3+2] by a base-promoted alkynylation and subsequent intramolecular addition reaction with aryl bromoacetylenes [50]. The synthesis of pyranonaphthoquinone derivatives has been reported in a multi-component one-pot reaction by a Knoevenagel reaction of malononitrile and aryl aldehydes followed by Michael addition of lawsone (Figure 9) [54]. Moreover, novel podophyllotoxin-naphthoquinone derivatives using microwave-assisted three-component reactions have been reported.…”
Section: Chemical Modification Of Nqs Structures With Nitrogen Groupsmentioning
confidence: 99%
“…The pentafluorophenyl derivative (Figure 7) showed activity against Toxoplasma gondii. In turn, a derivative of 3-chloro-4,5-dimethoxyphenyl, comparable to amphotericin B, turned out to be effective in the control of Leishmania major but it was also quite toxic to Vero cells [54]. The growing resistance and toxicity of current drugs are forcing researchers to seek alternative treatment options.…”
Section: Analogs Of Naphthoquinonementioning
confidence: 99%